Gastric outlet obstruction secondary to adult hypertrophic pyloric stenosis: case report and literature review - Calderón, Citlali; Belmont, Steve (International Journal of Research in Medical Sciences, 2024)
Adult hypertrophic pyloric stenosis is a rare entity; the most common type is secondary to underlying gastrointestinal pathologies, such as peptic ulcer, malignant tumors, and certain inflammatory diseases. A rare case of hypertrophic pyloric stenosis is presented in an adult patient secondary to acid peptic disease, presenting with gastric outlet obstruction, treated in the first instance with pyloric dilation successfully, however, the clinical picture has recurred now with 90% hypertrophic pyloric stenosis, it was decided to perform a surgical procedure with roux-en-Y gastrojejunal diversion, progressing with adequate evolution. There is no consensus on which is the most effective treatment. However, most authors seem to favor gastric resection due to the risk of malignancy secondary to long-standing hypertrophic pyloric stenosis.